National capitalisms, global production networks fashioning the value chain in the UK, USA, and Germany - Lane, Christel; Probert, Jocelyn (Oxford : Oxford University Press, 2009)
Firms in the clothing industry engage in global sourcing and operate in global markets. This title analyses the way British American and German firms in the clothing industry co-ordinate and govern their global production networks/value chains.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Clothing trade -- United States; Clothing trade -- Great Britain; Clothing trade -- Germany; Globalization -- Economic aspects